MBA in a nutshell - Sobel, Milo (McGraw-Hill, 2010)
You can learn the nuts and bolts of an MBA using this step-by-step guide. It's all here-- the essentials of marketing, accounting, finance, and more-- presented in the most clear and comprehensible way possible.